Pengembangan E-Modul Berbasis Pendekatan Problem Based Learning Untuk Meningkatkan Pemahaman Siswa Pada Pembelajaran Tematik Kelas V Tema 9 Subtema 3 SDN 107418 Bangun Sari Baru T.A 2022/2023 - Herzegovina, Lusitania; Perangin-Angin, Laurensia M.; Simbolon, Naeklan; Sitohang, Risma; Mailani, Elvi (Universitas Labuhanbatu, 2023)
This study aims to determine the validity of the feasibility, practicality and effectiveness of using Problem Based Learning (PBL) E-Modules in thematic learning class V Theme 9 Sub-theme 3 SDN 107418 Bangun Sari Baru. The method used in this study is R&D (Research and Development) using the ADDIE development model which consists of 5 stages namely Analysis, Design, Development, Implementation, Evaluation. In this study the product developed was the E-Module based on Problem Based Learning (PBL). The subjects in this study were clear V students at SDN 107418 Bangun Sari Baru, totaling 22 students. The objects in this study consisted of material experts, design experts and class teachers. The instruments used in this study were interviews, questionnaires and tests. The test questions used are pre-test and post-test. The results of the pre-test get an average score of 66.27 with the criterion